AN ANALYSIS OF CODE-MIXING USED IN NAJWA SHIHAB VIDEO MUDA BERSUARA PART 1 – PART 3 - Dewi Wulan Sari (Lembaga Penelitian Dan Pengabdian Masyarakat Institut Agama Islam Sultan Muhammad Syafiuddin Sambas Kalimantan Barat, 2022)
Code-mixing is the process of mixing or switching between one language to another language during the conversation. The aims of this research are to find out the type of code-mixing used in Najwa Shihab Video Muda Bersuara Part 1 – Part 3 and to find out the reason why code-mixing used in Najwa Shihab Video Muda Bersuara Part 1 – Part 3. The source of the data in this research are Najwa Shihab Video Muda Bersuara Part 1 – Part 3. Descriptive qualitative research method is used in this research. To achieve the result of this research, the researcher uses the theory about types of code-mixing from Muysken and the theory about the reason of why code-mixing is used by Hoffman. The result shows that there are 77 data. 41 data are categorized as insertion, 1 data is categorized as alternation and 35 data are categorized as congruent lexicalization. Meanwhile, 4 types of reason are found, they are talking about particular topic (49 data), being emphatic about something (23 data), repetition used for clarification (3 sata), and clarifying the speech content for interlocutor (2 data).